Total Testosterone Level is Lower in Women Consuming Combined Oral Contraception with Impaired Sexual Function - Yuniarty Amra; Joseph L Tumeida; Edi Hartono (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objectives: The aim of this research was to assess the relationship between total testosterone level and female sexual function based on Female Sexual Function Index (FSFI) among the acceptors of combined oral contraceptive pill. Methods: The research was conducted in BLU of Dr. Wahidin Sudirohusodo Hospital and several teaching hospitals in obstetrics and gynecology sections of Medical faculty, Hasanuddin University from October to December 2012. This study assessed sexual function among 60 women as the acceptors of combined oral contraceptive pill. Sexual function was assessed using FSFI questionnaire which had been validated in several countries. This research used cross sectional design and the sample was selected using consecutive sampling method. The data were processed using SPSS with independent t test of the significant level of 0.05. Results: The results of the research reveal that total testosterone level among the acceptors of combined oral contraceptive pill who have impaired sexual function is low. The result of the correlation test between testosterone level and FSFI score indicates a significant level (p<0.05) with a correlation coefficient of (r) = 0.737. The testosterone level of female who have impaired sexual function is significantly different (p<0.05) from women who have normal sexual function. The cut off testosterone level that could indicate the occurrence of sexual dysfunction is 12.4 ng/dl. Conclusion: The total testosterone level among the acceptors of combined oral contraceptive pill who have impaired sexual function is lower than others who have no impaired sexual function. [Indones J Obstet Gynecol 2013; 1-3: 129-33] Keywords: combined oral contraceptive pill, FSFI, sexual function, total testosterone level